O amor ἀγάπη como o caminho para exercer os dons carismáticos no corpo de Cristo: Uma análise e comparação exegética de 1 Coríntios 13 - Andreas Borchardt, Maiko (Vox Scripturae - Revista Teológica Internacional, 2012)
The research “the ἀγάπη love as the foundation to exercise of charismatic gifts in the body of Christ: an exegetical and comparative analysis of 1 Corinthians 13” wants to deepen the exegetical elements about ἀγάπη love in the biblical text of 1 Corinthians 13. First of all, the preliminary issues are emphasized in the letter of 1 Corinthians, as the city's history and the Christian community of Corinth, just as the conflicts and tensions existing there. In addition, the integrity of the letter, its authors, the recipients, the place of writing and timing are also discussed. In the second step, we analyze the biblical text of 1 Corinthians 13. This exegetical analysis, we seek to clarify details by analyzing and interpreting the text. Exegetical methods such as translation, compare translations, textual criticism, literary criticism, literary genre, grammar and structure analysis of the text are used. The scope of the text aims to condense the results. In the third step, exegetical work are compared with practical reflections of three authors: Heimbert Kunkel, Milton Schwantes and Luiz Henrique Scheidt. Among their interpretations of 1 Corinthians 13 are observed similarities, differences and particularities. Finally, from the three moments of the work, the conclusions are enrolled in this research.
Keywords: 1 Corinthians 13; ἀγάπη love; faith; hope; spiritual gifts; Corinth; conflicts